Expressing aspectual interactions in design : experiences in the slot machine domain - Fabry, Johan
In the context of an industrial project we are implementing the software of a casino slot machine. This software has a significant amount of cross-cutting concerns that depend on, and interact with each other, as well as with the modular concerns. We therefore wish to express our design using an appropriate Aspect-Oriented Modeling methodol- ogy and notation. We evaluated two of the most mature methodologies: Theme/UML and WEAVR, to establish their suitability. Remarkably, neither of these allow us to express any of the dependencies and inter- actions to our satisfaction. In both cases, half of the interaction types cannot be expressed at all while the other half need to be expressed using a workaround that hides the intention of the design. As a result, we consider both methodologies and notations unsuitable for expressing the dependencies and interactions present in the slot machine domain. In this paper we describe our evaluation experience.